The Effect of The Partial Solar Eclipse on Behavior of Three Species of Ardeidae In Rancabayawak Bandung - Johan Iskandar; Budiawati Supangkat Iskandar (Jurnal Biodjati, 2020)
The natural occurrence of solar eclipses can cause various impact on bird species. The purpose of this study was to examine the effect of the partial solar eclipses on changes in behavior of three species of Ardeidae in the Rancabayawak, Gedebage, Bandung, West Java. The research method used was qualitative which direct observation sampling technique was applied.  The results of study showed that three bird species of Ardeidae namely Javan Pond-Heron (Ardeola speciosa Horsfield 1821), Buffalo Egret (Bubulcus ibis Linnaeus 1758, and small egrets (Egretta garzetta Linnaeus 1766) with total population 566 individuals were recorded in the resting and breeding place of bamboo trees and surrounding area of Rancabayawak during the partial solar eclipse.The behavior of these tree bird species, including sound of chicks, sunbathing, preening the feather, and flying of individual adults went out the resting and breeding place of bamboo trees observed tend to be normal before occurring the partial solar eclipse. During the partial solar eclipse, however, the sound of the chick stopped for a second. Some individual adult birds stopped involve in preening their feather. While, some adult individual birds were flying go back to the nest of bamboo trees that may be assumed it has already late afternoon due to dark of sun shine. Implication of this research have been considered to be very important for contributing the scientific knowledge on bird behavior changes caused by natural phenomena of the partial solar eclipse.